A cost-effectiveness analysis of baloxavir marboxil versus oseltamivir for seasonal influenza treatment in China - Zheng, Fangyu; Tang, Yuekun; Jiang, Hongli (Frontiers in Pharmacology, 2026)
ObjectivesIn this study, we aimed to evaluate the cost-effectiveness of baloxavir marboxil versus oseltamivir for treating seasonal influenza among both high-risk and otherwise healthy populations in China from the healthcare system perspective.MethodsA decision tree model was constructed to evaluate the cost-effectiveness of two drugs. This model was integrated with a transmission dynamics model to assess the impact on controlling influenza spread. Model parameters for epidemiology, costs, and utilities were derived from real-world data on treatment costs from secondary and tertiary hospitals across China, the phase III clinical trial of baloxavir (CAPSTONE), and published literature.ResultsBaloxavir was found to be a dominant strategy compared to oseltamivir in both populations, yielding lower costs and higher QALYs. For the high-risk population, baloxavir treatment would save $2.5468 per patient and gain an additional 0.00018 QALYs. In addition, for the otherwise healthy population, it would save $1.1278 per patient and gain an additional 0.00024 QALYs. One-way sensitivity analysis identified QALYs for influenza and hospitalization costs as the most influential parameters for the high-risk population, whereas the number of infections, ICU fatality rate, and hospitalization costs were key drivers for the otherwise healthy population. Probabilistic sensitivity analysis confirmed the robustness of these findings.ConclusionBaloxavir is a cost-effective alternative to oseltamivir for seasonal influenza treatment in China. It can improve patient outcomes and reduce influenza transmission at a societal level, offering value to the healthcare system.